Analisis Semiotika Makna Motivasi pada Lirik Lagu “Teramini” Karya Ghea Indrawari - Salsah Anggraeni; Liliyana Liliyana; Fajar Muharam (Institut Nalanda, 2024)
The development of music in Indonesia has experienced growth and change from time to time, with unique and varied characteristics. As Indonesians, it is important for us to help preserve Indonesian music by supporting local musicians and appreciating their works. Music has an important role in culture and human life, not only as a means of entertainment and artistic expression, but also has a significant psychological and emotional impact on listeners. This research focuses on analyzing the motivational meaning of the lyrics of the song